Perspectivas da microgera????o e distribui????o de energia solar fotovoltaica no Brasil: um estudo prospectivo via minera????o de patentes - Jordani, Alan Rodrigo (2018)
Countries like Brazil faces problems in diversification of your energy matrix in function of your hidraulic potential and your priorization of your hidraulic energy by public policies over the decades. With higher costs of generation, transmission and distribution the cogeneration has been coming off with an oportunity to amplify its sources of renewable energy and search for energy efficiency. In this sense, one of the challenges at the moment and which constitutes the object of study in question is the identification of oportunities related to the utilization of photovoltaic solar energy still little explored in Brazil. This modality of energy has been receiving increasing attention in several countries, both of these that have a considerable index of insolation throughout the year and those that have reached a high standard of development in microgeneration and distribution technologies, involving cells and photovoltaic modules, networks of intelligent electric power, distributed generation and solar power plants. Successful world experiences of microgeneration and distribution involve photovoltaic systems connected to the distribution network, a situation that is likely to spread in Brazil. In addition to meeting the needs of the holders of the micro-generation units, this system may use the surplus to power the electric power networks and generate credit for a reduction in energy bills or the receipt of amounts by the offeror. The research question was as follows: how the technological trends are signaled by patent deposits involving photovoltaic cells at a global level related to microgeneration? With a view to answering this question, a technometric analysis, based on a survey and patent analysis, involving applications for patent deposits in microgeneration and microgrid of photovoltaic solar energy, panels, cells, silicon, and cadmium was conducted. This information extracted from the web via a data mining tool called Patent2net and had in perspective to identify technological trends that in the future may translate into new technologies that will enable the amplification of the use of photovoltaic solar energy in the Brazilian energy matrix. Special attention was given to the patents deposited in China, currently the country's largest producer of photovoltaic cells in the world. As Resolution Normative No. 687 of November 24, 2015 encourages the use of photovoltaic solar energy in Brazil, it is considered that the effective application of this legal diploma, may boost the production and distribution of photovoltaic solar energy in the country and create an environment favorable to the assimilation of future technologies that could result from patent applications that are now being deposited in several countries around the world. In the technometric analysis, four patent extractions were defined from which four patents were not protected in Brazil, for a more detailed analysis. In response to the research question, the result of the analysis of these four patents has shown that it is possible to identify patents involving innovations related mainly to equipment for the composition of devices and distributed microgeneration systems of photovoltaic solar energy. Among the four patents analyzed, the first one referred to an ultrafine and high efficiency photovoltaic cell; the second to a solar cell of high efficient heterogeny; the third to a thin-film solar cell roof; and the fourth to an intelligent photovoltaic microgrid distributed power generation system. In this sense, it is possible to say that Patent2net has proven to be an efficient search engine for patent information related to photovoltaic solar energy generation, which can be analyzed and used by Brazilian researchers and entrepreneurs for the development of technologies involving equipment comprising photovoltaic cells, making it possible to at least reduce the cost of replacing parts of these devices in the future.